Peningkatan Produktivitas Usaha Budidaya Ayam Kampung UKM Putra Budi Kecamatan Mojolaban Kabupaten Sukoharjo - Rendi Fathoni Hadi; Wara Pratitis Sabar Suprayogi; Eka Handayanta; Sudiyono Sudiyono; Aqni Hanifa; Susi Dwi Widyawati (PRIMA: Journal of Community Empowering and Services, 2021)
Increasing the Productivity of Kampong Chicken in the Putra Budi SME’s Mojolaban District Sukoharjo Regency. Putra Budi Small and Medium-Sized Enterprises (SMEs) located in Bekonang Village, Mojolaban Subdistrict, Sukoharjo Regency, is a business unit owned by Mr Apri with traditional kampong chicken breeding with a capacity of 50-100 chickens/period. Mr Apri. Putra Budi SMEs is engaged in traditional village chicken farming with a capacity of 50-100 chickens/period. Mr Apri started this business 5 years ago, but the maintenance method is still simple and has not been carried out intensively so that the productivity is low. Chicken sales are carried out on a wholesale basis, causing lower prices. Providing feed that does not meet the standard needs of livestock. The main problem faced by Putra Budi SME’s lies in the management of native chicken maintenance which includes management of feed, cages, sanitation, selection of broodstock, and hatching which are carried out traditionally (extensively). This service aims to increase the business of native chicken cultivation by implementing intensive cultivation, diversifying the marketing pattern of native chickens, and being able to increase partner income. Some of the solutions offered are to provide broader knowledge about the management of domestic chicken rearing which is still extensive/traditional towards programmed intensive management. The result of this service activity is that SME’s can apply feed management by selecting feed raw materials around the location and the practice of compiling quality native chicken rations, broiler-type chicken maintenance systems that are free from dangerous diseases/viruses, increasing productivity, efficiency, and speed of return on investment, and can establish cooperation with restaurants or SMEs processing native chicken. Based on the economic analysis carried out, the maintenance of the Putra Budi village chickens with 200 chickens experienced a 5% depletion and earned a profit of IDR 1,400,000 per breeding period.